2014
DOI: 10.1002/ange.201400218
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Silyl Ketene Acetals and Enol Ethers in the Catalytic Enantioselective Alkylative Ring Opening of Oxa/Aza Bicyclic Alkenes

Abstract: Silyl ketene acetals and enol ethers are employed as reactive and functional group tolerant nucleophiles in the enantioselective rhodium-catalyzed alkylative ring opening of a diverse class of oxa/azabicyclic alkenes. This method provides access to enantioenriched dihydronaphthalene and cyclohexene scaffolds, which have the potential to be derivatized toward core motifs of naphthoquinone and sesquiterpene natural products. Angewandte Chemie 6061Scheme 4. Azabicyclic alkene scope and derivatization. Absolute st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In other words, the THF acts as a co-catalyst in the system. The successful application of aprotic silyl ketene acetals and enol ethers, acting as the nucleophiles, also supported such a process16. Though it was found that the reaction of an alkoxide or phenoxide does not give ring-opened products18, our calculations showed that the alkoxide can poison the catalyst by coordinating to the central Rh metal (Figure S9).…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In other words, the THF acts as a co-catalyst in the system. The successful application of aprotic silyl ketene acetals and enol ethers, acting as the nucleophiles, also supported such a process16. Though it was found that the reaction of an alkoxide or phenoxide does not give ring-opened products18, our calculations showed that the alkoxide can poison the catalyst by coordinating to the central Rh metal (Figure S9).…”
Section: Resultsmentioning
confidence: 54%
“…This pioneering work has been regarded as a landmark in rapid access to chiral building blocks, as the resulting allylic compounds are important structural motifs in medicinal chemistry12. Since then, various nucleophiles were applied to this catalytic system including oxygen nucleophiles13, nitrogen nucleophiles14, sulfur nucleophiles15, carbon nucleophiles16 and halogen atoms17.…”
mentioning
confidence: 99%
“…Intramolecular hydroalkoxylation of the olefin moiety on alcohol 4a occurred with silver triflate [14] as the catalyst to give enantioenriched tetrahydrofuran derivatives 4band 4b' '.Although the diastereoselectivity of the hydroalkoxylation was low (1.1:1), each diastereomer was isolated in pure form with > 99 % ee. Carboxylic acid 4c underwent iodolactonization [15] to afford lactone 4d in 84 %y ield as as ingle isomer with > 99 % ee.…”
Section: Catalyticasymmetricallylicsubstitutionwithenolatesformsmentioning
confidence: 99%